Odpowiedzi

Najlepsza Odpowiedź!
2010-03-09T16:08:55+01:00
A)
8-(5-x)-4x=5(x+y)-3(x-y)=6-(5-x)-4x dla x=-2
8-[5-(-2)]-4(-2)=5(-2+y)-3(-2-y)=6-[5-(-2)]-4(-2)
8-(5+2)+8=5(-2+y)-3(-2-y)=6-(5+2)+8
8-7+8=-10+5y+6+3y=6-7+8
5y+3y=6-7+8-6+10-8+7-8
8y=2/:8
y=2/8
y=1/4

b)
8z-2(5z+6)+7z-4 dla z=¾
8*¾-2(5*¾+6)+7*¾-4=6-2(15/4+6/1)+21/4-4/1=6-2(15/4+24/4)+21/4-16/4=6-2*39/4+5/4=6-78/4+5/4=6-83/4=24/4-83/4=-59/4=-14¾

c)
4p-2(8p-p)+5p-p dla p = 1/2
4*½-2(8*½-½)+5½-½=2-2(4-½)+5=2-2*3½+5=2-5½+5=1½

d)
(x+y)-(x-y) dla x=0,75,y=-0,5
[0,75+(-0,5)]-[0,75-(-0,5)]=0,75-0,5-(0,75+0,5)=0,75-0,5-0,75-0,5=-1